MiR396 affects mycorrhization and root meristem activity in the legume Medicago truncatula. (3rd May 2013) - Bazin, Jérémie; Khan, Ghazanfar Abbas; Combier, Jean‐Philippe; Bustos‐Sanmamed, Pilar; Debernardi, Juan Manuel; Rodriguez, Ramiro; Sorin, Céline; Palatnik, Javier; Hartmann, Caroline; Crespi, Martin; Lelandais‐Brière, Christine
Summary The root system is crucial for acquisition of resources from the soil. In legumes, the efficiency of mineral and water uptake by the roots may be reinforced due to establishment of symbiotic relationships with mycorrhizal fungi and interactions with soil rhizobia. Here, we investigated the role of miR396 in regulating the architecture of the root system and in symbiotic interactions in the model legume Medicago truncatula. Analyses with promoter–GUS fusions suggested that the mtr‐miR396a and miR396b genes are highly expressed in root tips, preferentially in the transition zone, and display distinct expression profiles during lateral root and nodule development. Transgenic roots of composite plants that over‐express the miR396b precursor showed lower expression of six growth‐regulating factor genes (MtGRF) and two bHLH79‐like target genes, as well as reduced growth and mycorrhizal associations. miR396 inactivation by mimicry caused contrasting tendencies, with increased target expression, higher root biomass and more efficient colonization by arbuscular mycorrhizal fungi. In contrast to MtbHLH79, repression of three GRF targets by RNA interference severely impaired root growth. Early activation of mtr‐miR396b, concomitant with post‐transcriptional repression of MtGRF5 expression, was also observed in response to exogenous brassinosteroids. Growth limitation in miR396 over‐expressing roots correlated with a reduction in cell‐cycle gene expression and the number of dividing cells in the root apical meristem. These results link the miR396 network to the regulation of root growth and mycorrhizal associations in plants.